STUDY OF THE IMPACT OF BULLYING WITHIN THE OBLIGATORY SECONDARY EDUCATION, USING THE QUESTIONNAIRE CIMEI (AVILÉS, 1999)- QUESTIONNAIRE OF BULLYING- - Avilés Martínez, José María; Monjas Casares, Inés (Anales de Psicología / Annals of Psychology, 2005)
Using an evaluation´ questionnaire, the study measures the incidence of bullying in five schools of secondary education located in Valladolid.Result of this study is, the incidence related to victimisations and intimidations among students, the various ways of the mentioned intimidation and victimizations and the differences related to female/male and age between the 496 students analysed. The autopercepcion of the students shows that the incidence is similar to other nearly cultures. The various ways of bullying vary with the age, being the social exclusion and the mokery the most used forms at the last stage of education. Female and male have similar forms of practice of bullying, however boys attack more than girls. Number of victims is similar between boys and girls. Adults used not to be present when the bullying is done, usually in groups which in most cases are consenting of boys of the same classes.The students recognized that mostly the aggressor do not have to suffer for his/hers acts. Male teachers reacts more often than female teachers and mostly teachers react with young students.Victims and bullies are different in their causal attributions.